Patrimônio imaterial e as perspectivas de registro das rodas de capoeira – Santa Maria/ RS - Silva, Jorge Silveira da (2018)
This Master's thesis of the Postgraduate Program in Cultural Patrimony, Master level, of the Federal University of Santa Maria proposes as a final product the registration of the Capoeira wheels of the groups of Santa Maria, Rio Grande do Sul, due to their relevance as immaterial Brazilian heritage, with its aspects in the municipality, circumscribed to the practices of popular culture. Santa Maria is a Brazilian municipality located in the central-western region of Rio Grande, with 277,309 inhabitants, according to estimates by the Brazilian Institute of Geography and Statistics (IBGE, 2016), which has great influence in the central region of Rio Grande do Sul. understand the formation of a plural society with contrasts, differences and rich ethnic and cultural diversity, with significant cultural and historical heritage. In this diversity, we show the practice of Capoeira in Santa Maria, with an Afro-Brazilian heritage, which serves as an example of the Africans lived in the city. In this dissertation, it is proposed to analyze Capoeira as an Intangible Heritage and the prospects for registering the capoeira wheels in Santa Maria and the organization of a later inventory of the capoeira wheels in the city, which occur in the main spaces of sociability, public squares, popular culture and black collectives of the city. The research, registration and inventory criteria follow the rules of the Institute of Historical and Artistic Heritage of the State of Rio Grande do Sul (IPHAE). In this way, we understand that the Inventory becomes a possibility to safeguard it as an immaterial patrimony of Santa Maria. With the purpose of valuing this property in order to present the importance of the said group to the community and how it can contribute to a tourist attraction of the region. The product of the dissertation is based on Decree Law, no. 3,551 of August 4, 2000, which establishes the Register of Cultural Goods of Intangible Nature that constitute Brazilian cultural patrimony, creates the National Program of Intangible Heritage and provides other measures. The methodology used is theoretical research, case study, field work with interviews as data collection. The result proposes to carry out an inventory of the group, from the register, to find out to what extent the Santa Marian population values the cultural activities of capoeiristas.